A construção da imagem da mulher negra no Brasil através da arte: uma proposição de análise - Sousa, Mariana do Nascimento (2022)
This research problematizes the construction of the image of black women in Brazilian art between the 19th and 21st centuries. Therefore, we resorted to artistic works, of different modalities, periods and distinct authorship, with the objective of revealing the relationship between the images and the maintenance/subversion of the racial and gender symbolic regime in Brazil. One of the selected works is the caricature “The kiss of Ardit” by the French artist Joseph Mill, produced for the Rio de Janeiro magazine Bazar Volante in 1866. We point out the imperialism of the white-European perspective in the symbolic construction of the black feminine seen in the caricature. Likewise, we take the short story “Maria” by Conceição Evaristo (2018) to analyze, during the narrative, the author’s articulation against the permanence of the hegemonic gaze and on the black female body in contemporary times. As a methodological reference, we work in an intersectional way; the decolonial perspective developed by the Modernidade/Colonialidade collective, the trajectory of black feminist thought in Brazil and the concept of Control Images by Patricia Hill Collis (2019). These approaches, used in an intersectional way, contributed to the analysis of the selected artistic works. This is because the discussion about image based on the illustration 'O Beijo de Ardit', by Joseph Mill, and the short story 'Maria', by Conceição Evaristo, constituted the problematization that links the motivation of the research, the problem itself, and the theoretical plan. . Finally, we present the artistic work of contemporary Brazilian black women as a way to deconstruct the symbolic effects of colonialism on the black female body. After the theoretical discussion and analysis of the selected artistic works, it was concluded that just as the images of control were/are used by the ruling class to perpetuate the symbolic effects of colonialism, the images created by black women function as uncontrollable images. They deconstruct stereotypes created over centuries to attribute inhumanity, justify violence and control black female behavior. Soon they are a way of decolonizing the socially constructed look in the country.